Utilization of Interactive Multimedia for Drug Abuse Prevention in Social Studies At Elementary Schools - Nunuk Suryani, Achmad Basari Eko W, Mulyoto, Sri Anitah W dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Drug abuse has spread to all social class. The data of drug users among Elementary Schoolstudents were not as much detailed as those of drug users among students with highereducation and workers. Observing the cases reported by the print media and television,drug abuse among Elementary School students is increasingly rampant. Currently, thedevelopment of computer technology is utilized to all aspects in life. One of the aspects iseducation. The development of information technology can be applied in the production ofdrug abuse prevention interactive multimedia. It helps the students to study independently,mainly in Social Studies. Lastly the Social Studies in Elementary Schools is only merelyglued to rote learning so that the learning is less meaningful. A drug abuse preventioninteractive multimedia is therefore required in the Social Studies in Elementary Schools.An interesting interactive multimedia is expected to build the studentsâ learning motivationand to increase their understanding of drug abuse.Keywords: Interactive multimedia, drug prevention, Social Studies, Social Studies in ElementarySchools